(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
According to the importance of professional preparation of libraries and information, specialists in the field of improve the profession. The researcher conducted this study to recognize the reality of libraries and information education in Damascus University, which involves first-level university degree and high-level university degree (diploma- master-doctorate). The study contains the emergence and evolution of libraries and information education, recognizes study system and time period required to get the certificates, recognizes courses and analyze them, recognizes teachers and facilities and gives suggestions to develop libraries and information education. To achieve goals of study, the researcher used case study method as the best method in this situation. Data have been collected by a survey distributed to higher education students. Results came to adopt models to build, analyze, and evaluate courses and also to recognize the most important points of strength and weakness in libraries and information education in Damascus University. In addition of satisfaction degree of higher education students about the whole specialization.